Fashion Media and Sustainability Encouraging Ethical Consumption via Journalism and Influencers - Denisova, Anastasia (CAMRI Policy Briefs and Reports, 2021)
Fashion is among the biggest polluters, yet the media still promote throwaway fast fashion. The growing fashion public relations industry encourages and enables this media coverage. This policy brief identifies patterns in the way journalists and influencers cover fashion which contribute to unsustainable buying behaviours. Recent research recommends practical steps to improve media coverage to make consumption sustainable, by changing consumers' understanding and reducing the pressure on them to buy 'fast' satisfaction. Policy recommendations here suggested are based on original analysis of 1,000+ media artefacts in the UK - from magazines to newspapers, gossip weeklies to Instagram influencers. Researcher Anastasia Denisova proposes regulation of vocabulary and of affiliated links in journalism and social media, greater discussion of the psychology of buying and a 'paid advertisement label'. Also recommended is a more proactive approach to be taken by magazines and other media with the aim of promoting restyling advice and more sustainable coverage for readers of differing financial means.